Three-dimensional astrocyte-network Ni–P–O compound with superior electrocatalytic activity and stability for methanol oxidation in alkaline environments. Issue 8 (28th February 2015) - Tong, Y. Y.; Gu, C. D.; Zhang, J. L.; Huang, M. L.; Tang, H.; Wang, X. L.; Tu, J. P.
<x xml:space="preserve">Abstract</x> A self-assembly three-dimensional astrocyte-network Ni–P–O compound catalyzes methanol electro-oxidation in alkaline environments with superior electrocatalytic activity and stability.